A role for the pseudokinase HER3 in the acquired resistance against EGFR- and HER2-directed targeted therapy. (11th August 2014) - Claus, Jeroen; Patel, Gargi; Ng, Tony; Parker, Peter J.
Abstract : Specific inhibition of members of the EGFR (epidermal growth factor receptor) family, particularly EGFR and HER2 (human epidermal growth factor receptor 2), are an important therapeutic strategy in many human cancers. Compared with classical chemotherapy, these targeted therapeutics are very specific and initially effective, but acquired resistance against these targeted therapies is a recurring threat. A growing body of recent work has highlighted a pseudokinase in the EGFR family, HER3, and its ligand, NRG (neuregulin β1), to be of importance in models of resistant cancers, as well as in patients. In the present article, we describe some of the roles in which HER3 can mediate acquired resistance and discuss the current efforts to target HER3 itself in cancer.